2017
DOI: 10.1080/08820139.2017.1360342
|View full text |Cite
|
Sign up to set email alerts
|

Serum IL-6 and IL-8 Correlate with Prognostic Factors in Ovarian Cancer

Abstract: The aim of the study was to correlate serum levels of IL-2, IL-5, IL-6, IL-8, IL-10, and TNF-α with clinical, laboratory, and pathological prognostic factors in patients with primary ovarian malignancy. Patients treated at the Pelvic Mass Ambulatory of the Discipline of Gynecology and Obstetrics/Oncology Research Institute (IPON) of the UFTM with confirmed diagnosis of malignant ovarian neoplasia (n = 26) were evaluated. Serum collection was performed preoperatively for the determination of tumor markers. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 42 publications
6
53
0
2
Order By: Relevance
“…This suggests that IL6 secretion is enhanced in RNF20-depleted cells, which could stimulate autocrine and/or paracrine signaling to modulate the tumor microenvironment and promoting tumor progression. In line with our data, previous studies have shown that high IL6 in HGSOC is correlated with therapy resistance and poor prognosis (36,37). Mechanistically, it is likely that IL6 is operating through the JAK/STAT pathway in FT cells, but further studies are needed to define the precise intracellular response to IL6 in FT cells (38).…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that IL6 secretion is enhanced in RNF20-depleted cells, which could stimulate autocrine and/or paracrine signaling to modulate the tumor microenvironment and promoting tumor progression. In line with our data, previous studies have shown that high IL6 in HGSOC is correlated with therapy resistance and poor prognosis (36,37). Mechanistically, it is likely that IL6 is operating through the JAK/STAT pathway in FT cells, but further studies are needed to define the precise intracellular response to IL6 in FT cells (38).…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, ascites was not detected in the BAM and EM patients. Recent studies also propose that increased serum levels and peritoneal cavity levels of both IL-6 and IL-10 are associated with factors of worse prognosis in ovarian cancer patients [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Despite greater insights into the etiology of OHSS, the exact pathomechanism remains unclear. It has been hypothesized that local vasoactive mediators, such as vascular endothelial growth factor (VEGF), substances belonging to the renin-angiotensin system, and cytokines such as interleukin (IL)-6 and IL-8, play major roles in disease pathogenesis [5][6][7][8][9]. These factors can potentially induce fluid redistribution and massive extravasation, thereby resulting in a state of hypovolemic hyponatremia with hemoconcentration, as well as hypercoagulability [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…IL-8 levels of ovarian cancer, the increase in IL-8 levels was found to be related to the negative prognostic factors of ovarian cancer 18. …”
mentioning
confidence: 89%